Demography of Lung Cancer Patients: A Retrospective Study in Military Hospital, Dhaka - Elahi, Md Quadrat E; Razzak, Md Abdur; Islam, Md Azizul; Alam, Md Ashraful (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: The habit of smoking bidis and cigarettes is of long standing and widely prevalent in the southern part of Asia and largely in Bangladesh. Currently there are limited data on the lung cancer patients of Bangladesh. Objectives: To determine the correlation of smoking and lung cancer patients of CMH, Dhaka and to review their demographic profile. Materials and Methods: This retrospective hospital based study was conducted at Cancer Center, CMH, Dhaka. A total of 128 patients of lung cancer were enrolled those who were admitted to CMH Dhaka from January 2011 to December 2014. Data were collected in a predesigned format from old documents. Results: Age range of 128 lung cancer patients were from 28 to 80 years. Most of the patients 114(89.06%) belonged to >50 years age group, male 105(82.03%), 106(82.8%) smoker, 14(10.94%) were non-smoker and in 8 (6.25%) cases the smoking habit was not mentioned in documents. Most of the patients 60(47.24%) were from Dhaka district and belonged to lower middle class background 110(85.93%). Common coexisting diseases were COPD 30(23.43%), HTN 32(25%) and DM 25(19.53%). Maximum lung cancer cases were squamous cell subtype 38(29.69%) and adenocarcinoma 35(27.43%). TNM stage group IIIA were 25(19.53%), IIIB 40(31.25%) and IV were 35(27.34%). Large majority of patients were treated with chemotherapy alone 89(66.42%) and concurrent chemotherapy and radiotherapy 31(24.13%). Most of the patients of lung cancer 123(96%) died within 2 years of diagnosis. Conclusion: In this study, there was a strong correlation between smoking and lung cancer. Majority were diagnosed late in advanced stage and treated with chemotherapy alone or chemotherapy and radiotherapy combined. Prognosis was poor in this series and 96% died within 2 years of diagnosis. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 32-34